2021
DOI: 10.1186/s13002-021-00493-6
|View full text |Cite
|
Sign up to set email alerts
|

Species perceived to be dangerous are more likely to have distinctive local names

Abstract: Background Species with direct uses, such as sources of food, shelter, building material and medicine tend to have more specific local names. But could the same apply for species that people fear? Methods To address this question, here we explore the behavior and perception of species diversity and dangerousness through a survey of 1037 households in nine villages in Cabo Delgado, northern Mozambique. We compare people’s knowledge of snakes with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…Hunting poses significant risks, arising from the removal of reptiles from the wild for purposes such as food, "traditional" medicine, curios, and the pet trade. Additionally, reptiles face threats from unintentional by-catch during other harvesting activities, increasing instances of road mortality (Sparling et al, 2010), and persecution (Farooq, Bero, et al, 2021). These results also match expert opinion on reptiles which identified land use change, production and consumption, and human population as the main drivers for reptile loss (Isbell et al, 2023).…”
Section: 1patterns Of Threat At the Global Scalesupporting
confidence: 55%
“…Hunting poses significant risks, arising from the removal of reptiles from the wild for purposes such as food, "traditional" medicine, curios, and the pet trade. Additionally, reptiles face threats from unintentional by-catch during other harvesting activities, increasing instances of road mortality (Sparling et al, 2010), and persecution (Farooq, Bero, et al, 2021). These results also match expert opinion on reptiles which identified land use change, production and consumption, and human population as the main drivers for reptile loss (Isbell et al, 2023).…”
Section: 1patterns Of Threat At the Global Scalesupporting
confidence: 55%
“…It must also be noted that this variable entails some circularity, given that humans tend to assign common names to popular species and/or those that are relevant to humans in some way. For example, a recent study showed that across nine local villages in Mozambique, species perceived as dangerous were more likely to have a local name ( Farooq et al, 2021 ). Interestingly, this speaks about the possible existence of specific interactions among different cultural traits and cultural settings which our results do not capture and could be further explored with targeted studies.…”
Section: Discussionmentioning
confidence: 99%
“…We do this for three socioeconomic pathways that represent different distinct human population trajectories that are each based on multiple socioeconomic predictions (Olén & Lehsten, 2022). Our results provide a first assessment of the potentially threats of human expansion to one of the most persecuted taxa globally (Ceríaco, 2012;Langley et al, 1989;Liordos et al, 2018;Mesquita et al, 2015;Vaughn et al, 2022;Whitaker & Shine, 2000), especially in Africa (Farooq et al, 2021;Onyishi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Snakes in Africa account for 20,000 to 32,000 human deaths yearly (Gutiérrez et al., 2017), a figure that is likely to be considerably underestimated due to snakebite underreporting in many rural areas (Farooq et al., 2022). This has led to indiscriminate killing of snakes in many areas where people are experiencing frequent snake‐related deaths regardless of whether the specific species poses any real danger (Farooq et al., 2021). Thus, it is very likely that snakes, more than most other species groups, will be at an increased risk following human population expansions, even at low density of people (Fischer et al., 2012).…”
Section: Introductionmentioning
confidence: 99%